Utilization of Glycerol from Used Oil as an Ester Glycerol Surfactant - Dian Wardana; Ahmad Ramadhan; Dinda Prihatini Fitri Amne; Eddiyanto Eddiyanto (Indonesian Journal of Chemical Science and Technology (IJCST), 2019)
The development of biodiesel which is currently increasing has helped increase glycerol as a by-product. The glycerol can be obtained from a transesterification reaction in either vegetable or animal oils or fats and even used cooking oil. Glycerol buildup without further processing can reduce the selling price of glycerol. One solution to overcome this is to convert it to surfactants such as glycerol esters which are widely used in various industries such as chemistry, food, cosmetics, medicine and textiles. This study aims to utilize used cooking oil as a source of glycerol used in the synthesis of glycerol ester surfactants, as well as to compare the quality of glycerol ester surfactants produced by the use of commercial glycerol. The process begins by isolating glycerol from used cooking oil and then purifying it to improve its quality. Then glycerol ester was synthesized by using stearic acid, palmitic acid and oleic acid at reaction times of 120, 150 and 180 minutes. The highest yield of ester glycerol produced was at the reaction time of 180 minutes for each use of fatty acids. The test results showed that the glycerol ester produced was able to reduce the surface tension of the water. The value of hydrophylic-lipophylic balance (HLB) is not much different in the range of 5, and the use of various fatty acids and different sources of glycerol results in % of the stability of different emulsions.